Maze solution device with Stewart’s platform and OpenCV (2020)
This article presents the analytic study of the kinematics model for a Stewart’s platform; its includes the derivation of closed-loop expressions for the inverse Jacobian matrix of the mechanism and its derived time domain. A physically prototype platform was implemented to generates control with an artificial vision system executed in OpenCV library. The results includes the estimation of behaviour of the mobile platform and its mathematical relationship. The mathematical model and simulations of OpenSource were evaluated initially in Matlab, to finally perform an automatic maze labyrinth solution on top of the platform.